Compensatory health beliefs and unhealthy snack consumption in daily life. (1st February 2021) - Amrein, Melanie A.; Scholz, Urte; Inauen, Jennifer
Abstract: Compensatory health beliefs (CHBs) are beliefs that an unhealthy behavior (unhealthy eating) can be compensated for by engaging in a healthy behavior (physical activity). Previous research focused on CHBs as rather stable beliefs (trait). Some studies indicated that situation-specific CHBs (state) might be important in situations, in which people are confronted with an unhealthy snack. This study aims to investigate the association between CHBs and unhealthy snack consumption in daily life with a special focus on the distinction between trait and state CHBs. Overall, N = 45 participants (66.7% female; age: 18–45 years, M = 21.9) received a link to an online questionnaire five times daily for seven consecutive days ( n = 1575 possible diary entries). They reported unhealthy snack consumption, state and trait CHBs concerning the compensation with subsequent eating behavior and physical activity. The results showed that trait and state CHBs were significantly positively related to unhealthy snack consumption in daily life. Different effects appeared for CHBs concerning the compensation with subsequent eating behavior compared to the compensation with physical activity. This study demonstrates that both, state and trait CHBs are important for unhealthy snack consumption in daily life. Findings emphasize the need for further daily diary approaches to understand the temporal sequence of state CHBs that could further explain the use of CHBs as a maladaptive strategy for unhealthy eating.